A European empirical study of the relationship between firms' intellectual capital, financial performance and market value. Issue 4 (9th October 2017) - Sardo, Filipe; Serrasqueiro, Zélia
Abstract : Purpose: The purpose of this paper is to analyze the relationship between firms' intellectual capital (IC), financial performance (FP) and market value (MV) as well as the relationship between ownership concentrations on IC performance. Design/methodology/approach: A large sample of non-financial listed firms belonging to 14 countries in Western Europe, for the period between 2004 and 2015, was investigated using the GMM system (1998) dynamic estimator and the effect of lagged explanatory variables on firm's FP and MV. Findings: The results reveal that IC is an important resource for firms' value creation. Human capital is found to be a key factor of firms' wealth. Results show that capital employed efficiency positively impacts on firms' FP in the short run. The impact of IC components on firms' MV may not be immediate. The structural capital positively affects firms' FP in the long run. Also, the results reveal that ownership concentration and owners' management involvement constrain firms' IC performance. Originality/value: The current study contributes to IC research by exploring a large sample of firms across countries in Western Europe using econometric modeling. Considering that the effect of IC on firms' FP needs time to be realized, thus to be measured, the effect of lagged explanatory variables on performance was tested, using dynamic panel estimators, specifically the GMM system (1998) dynamic estimator.